ANALISIS INFILTRASI BERBAGAI UNIT LAHAN YANG BERBEDA PADA SUB DAS BANYU IRANG DAS MALUKA - Banjarina, Friska Aprilia; Badaruddin, Badaruddin; Kadir, Syarifuddin (JURNAL RIMBA LESTARI, 2021)
The purpose of this study is to analyze the infiltration rate in land units with different types of land cover in the Banyu Irang Sub Watershed in the Maluka Watershed. Analyzing the volume and infiltration capacity of land units with different types of land cover in the Banyu Irang watershed in the Maluka Watershed. The method used in this research is the Horton method. Factors affecting infiltration are soil texture, soil bulk density, total soil porosity, soil organic matter, and soil moisture content. The results of the study show the value of the rate, volume dan capacity of infiltration, where the highest infiltration rate is found in the secondary forest land cover with a value of 145,5 mm/hr on land unit 19 with slope grade between 0-8% and the lowest infiltration rate is found in alang-alang (reeds) land cover with a value of 3,0 mm/hr on land units 32 with slope grade between 15-25%. The highest infiltration capacity and volume occurred in secondary forest land cover with a value of 83,490 mm/hr in land units 19. The lowest infiltration capacity and volume occurs in alang-alang (reeds) land cover with a value of 0,787 mm/hr on land units 1 and 0,846 mm/hr on land units 1.